Mc. Donald’s Sebagai Sarana Propaganda Amerika di Dunia - Yusuf, Rusydi Muhammad; Trisno Adi, Bambang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Propaganda is a form of planned communication that contains messages that have been designed in such a way with the aim of influencing the attitudes, behavior and emotions of the propaganda target in accordance with what the propagandist wants to hope for, a means of propaganda used by the government to provide an image of a country. America as a large country in providing imagery also makes propaganda efforts, one of which is through fast-food advertisements, especially Mc Donald's. With various forms of advertisements displayed, America hopes that other countries will know that America is a big country that needs to be reckoned with. The method used in this research is descriptive analytical method. The technique of collecting data is by conducting literature and literature studies with the hypothesis that McDonald's fast-food advertisements are quite an effective tool for conveying propaganda. As a conclusion in this research, through fast food advertisements, Mc Donald's America has succeeded in raising its image in the international world as a big country both in the economic and military fields